Criminal Policy on the Distribution of Pornographic Content Through Electronic Media - Ingrid Angelina Lukito Arif; Nynda Fatmawati O (Dinasti Research, 2025)
The dissemination of pornographic content in cyberspace represents a complex challenge arising from advancements in information and communication technology. This content is widely accessible and distributed through social media and instant messaging platforms, presenting significant obstacles in law enforcement and criminal accountability. In Indonesia, the dissemination of pornographic content is regulated under Law No. 44 of 2008 on Pornography and Law No. 11 of 2008 on Information and Electronic Transactions (ITE). These laws prohibit the creation, distribution, and access to pornographic materials, with clear criminal sanctions for violators. Two models of liability are addressed: individual and corporate. Individual accountability involves actions such as uploading content, while corporate liability pertains to platforms facilitating its dissemination. Enforcement challenges include user anonymity and resource limitations among law enforcement agencies. To address this issue, preventive measures such as public education on the dangers of pornography and involvement of internet service providers in monitoring illegal content are crucial. International cooperation is also essential to tackle cross-border violations. With collective efforts, the spread of pornographic content can be mitigated. Effective prosecution, based on the relevant legal framework, is imperative to deter violations, protect society, and foster a safer cyberspace environment.